THE EFFECT OF ORGANIZATIONAL COMMITMENT AND LOCUS OF CONTROL ON THE PERFORMANCE OF THE VCI SUPERVISORY AGENCY WITH TRI KAYA PARISUDHA AS A MODERATING VARIABLE - Widiari, Ni Nyoman Opi; Suputra, I.D.G Dharma; Sudana, I Putu; Suartana, I Wayan (The journal of contemporary issues in business and government, 2021)
The Village Credit Institution (VCI) plays an important role for indigenous village communities, because the Village Credit Institution (VCI) is present as a solution to the problems of poverty alleviation programs and provides access to capital for small businesses. The phenomenon of corruption cases involving the chairman of the Village Credit Institution Supervisory Agency (VCI) that occurred recently added to the long list of corruption cases involving the chairman of the Village Credit Supervisory Agency (VCI). This study aims to examine the effect of organizational commitment and locus of control on the performance of the supervisory agency and Tri Kaya Parisudha as moderator.This research was conducted at the Village Credit Institution in Badung Regency using primary data obtained from questionnaires. The method of determining the sample using a quota sampling technique with respondents obtained as many as 81 of 90 respondents at the Village Credit Institution in Badung Regency. The data analysis technique used is the interaction test1304variable moderation moderated regression analysis (MRA).Results analysis shows that organizational commitment has a positive effect on the performance of the VCI supervisory body, locus of control has a positive effect on the performance of the VCI supervisory body, Tri Kaya Parisudha strengthens the influence of organizational commitment on the performance of the VCI supervisory body, and Tri Kaya Parisudha strengthens the influence of locus of control on the performance of the supervisory body. VCI.